3D Network‐Assisted Crystallization for Fully Printed Perovskite Solar Cells with Superior Irradiation Stability. (15th July 2022) - Li, Feng; Gong, Chenxiang; Fan, Baojin; Xing, Zhi; Meng, Xiangchuan; Zhang, Shaohua; Hu, Xiaotian; Chen, Yiwang
Abstract: Meniscus‐coating as a high‐throughput preparation process has significant advantages in the manufacture of large‐area perovskite solar cells (PSCs). However, the gradient crystallization during printing significantly affects the vertical uniformity of perovskite films, which greatly affects the carrier transport of perovskite films and the stability of PSCs. Here, a perovskite ink compatible with printing technology is reported to realize uniform printing of perovskite film on a 3D scale. The siloxane 3D network hinders the solute migration caused by capillary force and acts as a skeleton to promote the uniform crystallization of perovskite films. Consequently, the corresponding fully printed PSCs have reduced efficiency loss (from 37.4% to 17.0%). In addition, based on the improvement of crystal quality and reduction of defects in perovskite films, the siloxane‐optimized PSCs achieved a championship efficiency of 22.0%, which is one of the highest performance for fully printed devices. The optimized device retains 80% of the initial PCE after 800 h AM 1.5G one‐sun illumination, and only decreases 20% after 160 h of ultraviolet light (365 nm, 20 mW cm −2 ) irradiation. Abstract : The introduction of a siloxane 3D network assists the crystallization of the perovskite liquid film, resulting in vertically uniform and high‐quality perovskite films. This strategy significantly improves the homogeneity and bottom crystalline quality of perovskite films, which reduces the efficiency loss of perovskite solar cells (PSCs) and enhances the irradiation stability of PSCs. With this strategy, the PCE of the small‐area devices and modules prepared by full printing is 22% and 16.51%, respectively.